Novel investigation on tensile strength, compressive strength, hardness, and corrosion resistance of Al6061 hybrid composite with 15 % weight fraction of Silicon carbide and Fly ash and comparing the outputs with as-cast Aluminium 6061 (Journal of Pharmaceutical Negative Results, 2022)
Aim: The aim of this research is to fabricate an aluminium hybrid metal matrix composite reinforced with a 15% weight fraction constituting 7.5% of silicon carbide and 7.5% of fly ash using the stir casting method under controlled process parameters and compare tensile strength, compressive strength, hardness and corrosion resistance with pure as-cast Aluminium 6061. Materials and Methods: Samples of dimensions 150mm x 150mm and thickness 10mm are prepared under Identical conditions adhering to standards. For g power calculations (threshold level: 0.20, confidence interval: 80%) gives a sample size of 80. Mechanical tests are taken individually on each sample for 20 samples of the experimental group (AHMMC) and control group (As-cast AL6061) as per ASTM standards. Results: One-way ANOVA using SPSS software shows that AHMMC with a 15% weight fraction of SiC and Fly ash has a significantly higher tensile strength (38.97 MPa), compressive strength (55.91 kN), and hardness (76 HV) but has slightly lower corrosion resistance (1.659 mm/year) than that of as-cast Al6061 with a significance level of 0.036 (p<0.05). Conclusion: Within the limitations of this study, It is revealed that AHMMC with a 15% weight fraction of SiC+Fly ash exhibited enhanced Mechanical and physical properties when compared to as-cast Al6061.